Exploring the Effectiveness of Descriptive Texts in Teaching the Simple Present Tense - Cut Mawar Helmanda; Siti Safura; Rahmatun Nisa (Yayasan Al-Afif, 2025)
Mastering the simple present tense remains a challenge for many students, particularly in constructing sentences and distinguishing between verbal and nominal forms. This study aims to explore the effectiveness of descriptive texts in facilitating students’ understanding of the simple present tense and to identify the difficulties they encounter. A qualitative research design was employed, using classroom observation and student interviews as the primary instruments. The research was conducted in the Department of English Education at Universitas Muhammadiyah Aceh with 15 student participants. The findings reveal that descriptive texts provide meaningful contexts that enhance students’ comprehension and application of the simple present tense. However, students still face problems such as sentence construction errors, limited grammatical accuracy, and difficulties in applying rules consistently. These results suggest that descriptive texts are a valuable medium for teaching grammar, offering pedagogical insights for improving language instruction in higher education.